Effective Leadership: Determinant of Culture, Age and Gender in Eldoret Town - Oling’a, Thomas D. (IJRDO - Journal of Applied Management Science, 2015)
The paper aims to understand the concept of effective leadership and the effects of culture, age, andgender on leadership in Eldoret Town. A sample of nine leaders from diverse backgrounds includingChina was interviewed using a standard questionnaire to bring out detailed aspects of leadershipwhich include cultural intelligence, competencies and personal effectiveness. The findings indicatethat there were no significant differences in leadership behavior between males and females.However, older leaders were more averse to risk taking and technophobic, contrary to youngerleaders who value independence and flexibility. Some of the traits mentioned were attributed toeffective leadership styles. Based on the current results and literature review, a holistic Leadershipmodel was constructed for development of effective leaders